The Influence of Information Technology Utilization and Classroom Supervision on Teacher Performance at SMA Negeri 1 Lempuing OKI - Agung Romanto; Bukman Lian; Dessy Wardiyah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to determine how information technology and class supervision affect teacher performance at SMA Negeri 1 Lempuing, Ogan Komering Ilir Regency. To achieve this goal, research was carried out using descriptive quantitative methods; the population and sample consisted of 54 teachers, and the technique of collecting data was using documentation and questionnaires. The operational definition of the variables of information technology utilization (